Heart Rate and Cardiovascular Responses to Commercial Flights: Relationships with Physical Fitness - Oliveira-Silva, Iransé; Leicht, Anthony S.; Moraes, Milton R.; Simões, Herbert G.; Del Rosso, Sebastián; Córdova, Cláudio; Boullosa, Daniel A. (Frontiers in Physiology, 2016)
The aim of this study was to examine the influence of physical fitness on cardiac autonomic control in passengers prior to, during and following commercial flights. Twenty-two, physically active men (36.4±6.4 years) undertook assessments of physical fitness followed by recordings of 24-hours heart rate (HR), heart rate variability (HRV) and blood pressure (BP) on a Control (no flight) and Experimental (flight) day. Recordings were analysed using a two-way analysis of variance for repeated measures with relationships between variables examined via Pearson product-moment correlation coefficients. Compared to the Control day, 24-hours HR was significantly greater (>7%) and HRV measures (5-39%) significantly lower on the Experimental day. During the 1-hr flight, HR (24%) and BP (6%) were increased while measures of HRV (26-45%) were reduced. Absolute values of HRV during the Experimental day and relative changes in HRV measures (Control-Experimental) were significantly correlated with measures of aerobic fitness (r = 0.43 to 0.51; -0.53 to -0.52) and body composition (r = -0.63 to -0.43; 0.48-0.61). The current results demonstrated that short-term commercial flying significantly altered cardiovascular function including the reduction of parasympathetic modulations. Further, greater physical fitness and lower body fat composition were associated with greater cardiac autonomic control for passengers during flights. Enhanced physical fitness and leaner body composition may enable passengers to cope better with the cardiovascular stress and high allostatic load associated with air travel for enhanced passenger well-being.